Penerapan Komunikasi Non Verbal Dalam Permainan Tradisional Anak - Fitrianola Rezkiki; Imelda Rahmayunia Kartika; Rina Mariyana; Hauzan Jiyad Adli (Surya Edukasi: Jurnal Pengabdian Masyarakat, 2025)
Traditional games are a form of play therapy for children to increase motor skills. The application of non-verbal communication when playing can make children comfortable and stimulate children to understand the concept of the game more quickly. The aim of this community service is to see the application of educators' non-verbal communication in children's traditional games, especially in seeing children's growth  and development. The methods used in this PKM include; sharing information about the application of non-verbal communication in the traditional game "hi hi smart child", demonstrations to educators and kindergarten/PAUD children, and implementation of games by assessing children's motor skills before and after traditional games accompanied by non-verbal communication. The PKM results show that there is an increase in children's gross motor skills like speed and agility after being given traditional games accompanied by non-verbal communication. It is hoped that the TK/PAUD can continue this activity and carry out continuous evaluations, so that they can improve the quality of children's growth and development.